Lymphatic clearance is the main drainage route of lamotrigine-loaded micelles following delivery to the brain. (17th July 2019) - Yan, Jiaqi; Ren, Jialin; Zhu, Yu; Lin, Yanzhen; Chen, Gang; Hou, Dongzhi; Lv, Zhufen; Zhou, Jiaxin; Chen, Yanzhong; Yang, Fan
Abstract: Objectives: This study aimed to investigate the clearance pathways of lamotrigine (LTG)-loaded micelles by intranasal administration and intracerebral injection in the brain and whether nanoparticles can induce the inflammation promoted by interleukin-6 (IL-6), accelerating the phagocytosis of drug particles in the brain and drainage through lymphatics. Methods: The drug concentrations in the deep cervical lymph node, superficial cervical lymph node, brain tissues and jugular vein, the pharmacokinetic parameters, and the concentrations of IL-6 in deep cervical lymph node and brain tissues were investigated following UPLC/MS, DAS3.0, ELISA statistically analysed. Key findings: The AUC0– t of deep cervical lymph node after intranasal and intracerebral injection was 1.93, 2.77, 1.34 times and 3.06, 16.4, 3.34 times higher compared with the superficial cervical lymph node, jugular vein and brain tissue, respectively. After intranasal administration of lamotrigine-loaded micelles for 30 min, the IL-6 concentrations in deep cervical lymph node and brain tissue were significantly increased ( P < 0.05). Conclusions: These results suggested that lamotrigine micelles were primarily cleared from the brain by lymphatics rather than blood clearance. Also, the nanoparticle induced the increase in IL-6 level after entering the brain suggested that nanoparticles might induce the inflammation promoted by IL-6 in the brain, accelerating the clearance of drug particles in the brain and drainage through lymphatics.